The Influence of Learning Models cooperative Make a Match type and media based Canva app against level HOTS thinking of students - Amelia, Tria; Amus, Sunarto; Suyuti, Suyuti (Journal of Education Method and Learning Strategy, 2024)
Build existence The Indonesian nation with character in the 21st century is challenge for Indonesian nation. This model help student understand material in a way effective through card answers and games ask answer so that learning become more fun and not boring. Formulation problem is there is influence of learning models cooperative type Make a Match against level think HOTS students in the eyes social studies class IV Gugus RA Kartini, Bumi Raya District, Regency Morowali, Is there is media- based influence Canva app against level think HOTS students in the eyes social studies class IV Gugus RA Kartini, Bumi Raya District, Regency Morowali. Research purposes Analyze influence of learning models cooperative Make a Match type against level think HOTS students in the eyes social studies class IV Gugus RA Kartini, Bumi Raya District, Regency Morowali, Analyzing media- based influence Canva app against level think HOTS students in the eyes social studies class IV Gugus RA Kartini, Bumi Raya District, Regency Morowali. method study experiment is method research conducted​ with experiment, which is used For know influence variable independent ( treatment ) towards variable dependent ( result ) in controlled conditions.​ Research result Analysis statistics descriptive aim For describe achievement results Study so that known HOTS thinking level of students with apply the learning model cooperative Make a Match type in class experiment and use application media Canva- based classes control.